2011
DOI: 10.1002/eji.201141538
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular proteolysis in macrophage migration: Losing grip for a breakthrough

Abstract: Macrophage tissue infiltration is a hallmark of several pathological situations including cancer, neurodegenerative disorders and chronic inflammation. Hence, deciphering the mechanisms of macrophage migration across a variety of tissues holds great potential for novel anti-inflammatory therapies. Leukocytes have long been thought to migrate through tissues by using the amoeboid (protease-independent) migration mode; however, recent evidence indicates that macrophages can use either the amoeboid or the mesench… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 92 publications
4
62
0
Order By: Relevance
“…5A). Consistent with previous reports (Van Goethem et al, 2010;Vérollet et al, 2011), we found formation of elongated protrusions, which showed F-actin enrichment at their tips. Strikingly, the tips were also enriched in MT1-MMP-mCherry, pointing to a potential degradative capacity of these structures (Fig.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…5A). Consistent with previous reports (Van Goethem et al, 2010;Vérollet et al, 2011), we found formation of elongated protrusions, which showed F-actin enrichment at their tips. Strikingly, the tips were also enriched in MT1-MMP-mCherry, pointing to a potential degradative capacity of these structures (Fig.…”
Section: Introductionsupporting
confidence: 82%
“…Within tissues, however, cells are surrounded by a three-dimensional environment, which is expected to influence both regulatory pathways involved in matrix degradation as well as the matrix-degrading organelles themselves. Indeed, primary human macrophages in gelled collagen I matrix have been shown to form long, dynamic protrusions that enriched are at their tips in podosome components such as F-actin, cortactin, talin, vinculin and CD44 (Van Goethem et al, 2010;Vérollet et al, 2011). Colocalisation of these structures with matrix defects and also with fluorescence signals in the collagen dequenching assay support the idea that these structures exhibit degradative capacity (Van Goethem et al, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…TMJ disk displacement induces progressive degradation of connective tissue ECM and histopathological changes that eventually lead to permanent loss of function (Vérollet et al, 2011). Normal TMJ disk contains ECM macromolecules, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Migration in 3D dense matrices such as Matrigel requires ECM degradation for macrophages to create paths. 9 In these environments, macrophages form cell protrusions called 3D podosomes at the tip of which podosome proteins accumulate along with F-actin and matrix proteolytic activity.…”
mentioning
confidence: 99%